Analysis of Accountability in Village Fund Management to Enhance Community Welfare - Nurul Indah Q. Muksin; Driana Leniwati; Nurul Asfiah (Electronic Journal of Education, Social Economics and Technology, 2026)
This study examines the accountability of village fund management as a key determinant of rural community welfare in Indonesia, with a particular focus on villages that are highly dependent on intergovernmental transfers and face socio-economic vulnerability. Anchored in Public Accountability Theory, Good Governance, and Agency Theory, the research addresses a gap in prior studies that largely emphasize procedural compliance and transparency but seldom analyze how accountability dimensions are empirically related to welfare outcomes. The study aims to (1) assess the level of accountability across the stages of planning, budgeting, implementation, reporting, and oversight; and (2) examine the relationship between transparency, participation, legal compliance, effectiveness–efficiency, and public answerability with indicators of community welfare. Using a qualitative or mixed-method approach, data are collected through document review, interviews, and/or surveys involving village officials, community representatives, and relevant stakeholders. The findings are expected to demonstrate how strong accountability practices enhance the effectiveness of village fund utilization for infrastructure, social services, and economic empowerment, while weak accountability is associated with misallocation and limited welfare gains. The study contributes theoretically by integrating accountability, governance, and agency perspectives, and offers practical recommendations to strengthen local financial governance so that village funds more effectively promote equitable and sustainable rural welfare.